The value of Terramycin (TM-10) and Oleandomycin in the protein supplement for fattening spring pigs on alfalfa pasture - Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
The antibiotic, Oleandomycin, is a recent introduction. This experiment was to test the antibiotics value. Three lots of nine pigs each were self-fed shelled corn and a mixed protein supplement on alfalfa pasture. All three lots had the same mixed protein supplement of 4 parts tankage, 4 parts soybean meal, 1 part cottonseed meal, and 1 part alfalfa meal. 4 ½ pounds of Terramycin TM-10 and 4 ½ pounds of Oleandomycin were added per ton to the protein mixture of lot 2. Lot 3 pigs had 4 ½ pounds of Oleandomycin premix added per ton to their protein mixture.
Keywords: Swine; Terramycin; Oleandomycin; Protein; Alfalfa